Analisis Kemampuan Abstraksi Matematis Ditinjau dari Gaya Belajar Kolb Berbantuan Media Google Slides - Ucu Rosmiati; Ratnaningsih, Nani; Ni’mah, Khomsatun (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2021)
The purpose of this study was to describe students' mathematical abstraction abilities in terms of the types of learning styles diverger, accommodator, converger, and assimilator. This research is a qualitative research with research subjects namely students of class VIII SMP. Of the 16 research subjects, one subject was selected in each Kolb learning style group based onbasis purposive. The instruments used in this study were Kolb's learning style questionnaire, mathematical abstraction test questions, and interviews. Mathematical abstraction ability tests are given online viamedia google slides. Based on the data analysis, it is concluded that (1) Student with diverger learning styles can complete indicators of mathematical abstraction ability, except indicators make generalizations. (2) Student with an accommodator learning style can complete indicators of mathematical abstraction ability unless the indicator identifies the characteristics of the object being manipulated or imagined and the indicator makes generalizations. (3) Students with converger and assimilator learning styles can solve all indicators of mathematical abstraction ability.